INFLUENCE OF GENDER ON ETHICAL DECISION MAKING IN THE LEGAL PROFESSION: A CASE STUDY IN INDONESIA - Ananda, Putri; Nurwandri, Andri; utama, Herly; Aniza, Siti (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The study examines the influence of gender on moral judgment in the legal profession in Indonesia. In this study, gender gaps in the ethical decision-making process and the factors that influence them are identified through a qualitative approach and a survey of relevant literature. The findings of the study indicate that, despite significant barriers related to gender stereotypes, women in the legal field usually prioritize ethical principles when making decisions. To create more impartial and fair justice, this study disseminates information about the importance of gender equality in the legal system. Additionally, this study found that while there were no pronounced gender differences, women tended to be more vulnerable to the impact of emotions and social norms on moral judgment. This implies that even while gender has no direct bearing on moral judgments, social and emotional background must still be taken into account. With a focus on the necessity of a more inclusive and sensitive approach to the social elements that influence decision-making, these findings offer significant insights for the establishment of ethical rules and training in the Indonesian legal profession.